Proceedings 2001 IEEE International Conference on Data Mining
DOI: 10.1109/icdm.2001.989500
|View full text |Cite
|
Sign up to set email alerts
|

Who links to whom: mining linkage between Web sites

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0
2

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 17 publications
1
92
0
2
Order By: Relevance
“…Bharat et al [2] have shown that there are two different types of web links dominating the web structure, "intra-site" links and "inter-site" ones. A "site" can be a domain (.yahoo.com), a host (geocities.yahoo.com) or a directory on a web server (http://www.geocities.com/someuser/).…”
Section: Host-based Link Localitymentioning
confidence: 99%
“…Bharat et al [2] have shown that there are two different types of web links dominating the web structure, "intra-site" links and "inter-site" ones. A "site" can be a domain (.yahoo.com), a host (geocities.yahoo.com) or a directory on a web server (http://www.geocities.com/someuser/).…”
Section: Host-based Link Localitymentioning
confidence: 99%
“…The first papers to raise the issue were [27,18]. The spammers' success was noted in [2,9,10,11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Web spamming has received a lot of attention lately [2,3,10,11,15,17,18,20,23,26,27,30]. The first papers to raise the issue were [27,18].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the boundary of a web-site can automate the choice of pages to archive. Studying the world-wide web at web-site level rather than web-page level may also have useful applications [3].Documents can be represented by multiple pages on the web [5]. Thus, sometimes, it is not reasonable to study attributes like authorship at page level.…”
Section: Introductionmentioning
confidence: 99%